(3TQM GdcaGjIs - (3GdfLaj, GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3bhdg CbhGd ddCUMGH gPG QGLY Edi GdGSJUMGH hEdi MLjJg Cj Cf GdGSJUMGH ajg CbhGd MjK GNJdahG aj JYQjag haj MLjJg CbhGd MjK GNdJdahG ajgGs
(3BNQgG (B:s
(3BNQgG(B: (3bhdg hZjQ Pdc cMQeI GdVO hhLhH GdebOeI, bhdg Ydi GdKGHJ Cj Ydi GdhLhH GdKGHJ HZjQ GdGSJUMGH, gPG hbO hUd HfG GdcdGe Edi gPG GdebGes
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg aj fgGjI GdLRA GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs